A Conceptual and Legal Perspective on the Green Economy. Issue 1 (25th March 2013) - Morgera, Elisa; Savaresi, Annalisa
Abstract : The 2012 United Nations Conference on Sustainable Development had as one of its two main themes 'a green economy in the context of sustainable development and poverty eradication'. The Conference did not agree upon a definition of 'green economy' and limited itself to '[encouraging] each country to consider the implementation of green economy policies' as one of the different approaches available to achieve sustainable development. Nevertheless, its outcome document provides a host of indications about the challenges and opportunities to achieve sustainable development through the green economy. This article offers a conceptual and legal perspective on the green economy by investigating the evolution of the related policy debate and focusing on whether the text on the green economy adopted at Rio+20 provides new insights on the implementation of sustainable development, notably in relation to environmental integration, intra‐generational equity, human rights and corporate accountability.